A set covering model of recycling bins allocation in university campus - Nur 'Afiny, Jepri (2024)
Recycling systems can be defined as the processes involved in collecting recyclable waste and remanufacturing it into new products. Since the 1970s, the Malaysian government has been committed to improve this system through various ongoing efforts and initiatives. However, there has been insufficient support and engagement from the public, resulting the majority of recyclable waste ending up in landfills. Past research indicates that providing an optimal number of recycling bins at strategic locations, could enhance public support and engagement. This study aims to optimize the number of recycling bins in a university campus, specifically Universiti Utara Malaysia (UUM). Integer programming model of a set covering problem is employed to address the problem. This study considers three distance coverage options for recycling bin placement which are 100, 250, and 500 meters, involving a total of 105 locations in UUM. The optimal solution shows that 68 recycling bins are needed to cover all locations within 100 meters walking distance. For the distance of 250 meters needs 41 recycling bins while 500 meters requires 24 recycling bins. The proposed solutions may assist UUM management in providing an adequate number of recycling bins in UUM. In addition, the developed model can be applied to other university campus in optimizing the number of recycling bins. Providing a sufficient number of recycling bins across campus will make it more convenient for the university community to access them. This accessibility can encourage the practice of the 3R (reduce, reuse, and recycle) among university community, fostering a more sustainable campus environment.